EMPIRICAL REVIEW OF WOMEN PARTICIPATION IN SOME AGRICULTURAL SUB-SECTORS OF THE GLOBE - Jirgi, A. J.; Oluwafemi, R. A.; Oseghale, A. I. (Journal of Agripreneurship and Sustainable Development, 2020)
The study reviewed empirical studies on women participation in some agricultural sub-sectors of the globe. The sub-sectors considered in the study were crop production, livestock production and aquaculture. The study expressly disclosed that women are great assets for agriculture and if given adequate opportunity could be of great help in the achievement of food and nutrition security furthering in the adaptation and mitigation of climate change. Despite the prospects of women, their participation in the various agricultural sub-sectors is hindered by inadequate access to finance, inputs, extension services, market linkages, training and workshop amongst others. The study observed that women participated in crop, livestock and aquaculture enterprises but on a small scale producing mainly for household consumption, even though majority of the women studied by the researchers lacked formal education. The study, therefore, concluded that agricultural productivity can be improved if the gender gap between men and women was closed. The study recommended that women farmers should be involved in the decision-making processes and they should actively participate in the establishment of agricultural policies and programs both at the State, national and international levels.